Inventories and the Volatility of Production - Kahn, James A. (American Economic Review, 1987)
A stylized fact associated with inventory behavior is that the variance of production exceeds the variance of sales. This paper presents a model of production decisions with demand uncertainty that incorporates nonnegativity constraints on inventories. Even with no productivity shocks, optimal behavior by the firm is consistent with this stylized fact, either if demand exhibits positive serial correlation, or if the firm can backlog excess demand.